The association of anxiety and mood symptoms in patients with bipolar disorders attending follow-up treatment - Khalil Azizan, Mohammad Nabhan (2015)
Background: Anxiety is common in Bipolar Disorders (BD). It is associated with poorer outcome in BD, for example increased in relapse rate and hospitalization, suicidality, substance abuse and more severe symptoms of mania and depression. Malaysian study regarding anxiety in BD is still lacking. Objective: The aim of this study was to determine prevalence of significant anxiety and its detection rate in psychiatric outpatient clinic. Sociodemographic and clinical characteristics associated with anxiety were also examined. Correlation between anxiety and mood symptoms and the burden of life events within one-year period were measured. Method: This is a cross-sectional study done in psychiatric outpatient clinic in Hospital Universiti Sains Malaysia. Sociodemographic and clinical data were acquired from selected samples and four self-rated scales [Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), Young Mania Rating Scale (YMRS) and Social Readjustment Rating Scale (SRRS)] were administered to measure mood symptoms, anxiety symptoms and the burden of life events within the previous one year. Regression and correlation analysis were done to examine relationship between anxiety symptoms and mood symptoms and sociodemographic and clinical data. Results: 20.5% of the total 132 participants had significant level of anxiety. Among these, only 29.3% were detected by clinicians. Anxiety level (BAI) in BD was positively and independently associated with Bipolar II Disorder, number of relapse and BDI score. There was strong positive correlation between BAI and BDI (r = 0.690, p <0.001). There was weak positive correlation between BAI and SRRS (r = 0.194, p =0.026). Conclusion: Anxiety in BD is poorly detected by clinicians and was associated with Bipolar II Disorder, higher frequency of relapse, more severe depression, and more burdens of life event within one-year period. Clinicians need to be sensitive in detecting anxiety in BD. More research is needed in finding effective treatment for anxiety in BD.